Odyssey - Homer (Open Road Integrated Media, 2017)
The Ancient Greek tale of Odysseus, cursed to wander the perilous world on his epic voyage home. The decade-long Trojan War has come to an end and Odysseus, the King of Ithaca instrumental in securing victory for the Greeks, finally sets sail for home. But his adventures are far from over. Cursed by the god Poseidon to wander the earth for ten years, he must battle monstrous creatures-even facing the land of the dead-before returning to Ithaca, where still more dangers await him. In his long absence, Odysseus's wife, Penelope, and son, Telemachus, have endured a violent crowd of suitors who occupied the royal palace. Together with The Iliad, Homer's epic poem of the Trojan War, The Odyssey is one of the oldest surviving works of Western literature. Samuel Butler's beautiful English prose version, first appearing in 1900, remains one of the most beloved and acclaimed translations of this timeless tale. This ebook has been professionally proofread to ensure accuracy and readability on all devices.